Comprehensive Analysis of Pathogenic Deletion Variants in Fanconi Anemia Genes. Issue 11 (November 2014) - Flynn, Elizabeth K.; Kamat, Aparna; Lach, Francis P.; Donovan, Frank X.; Kimble, Danielle C.; Narisu, Narisu; Sanborn, Erica; Boulad, Farid; Davies, Stella M.; Gillio, Alfred P.; Harris, Richard E.; MacMillan, Margaret L.; et al.
<x xml:space="preserve">Abstract</x> We report results from screening 202 Fanconi anemia (FA) families for large deletions. High‐resolution analysis of the deletion boundaries identified by aCGH, accompanied by subsequent cloning and sequencing of the breakpoints, revealed that 52 FANCA deletionends, and one FANCC deletion end extended beyond thegene boundaries, potentially affecting neighboring geneswith phenotypic consequences. We also gainedinsight into the location and potential mechanisms driving the intrachromosomal breakage events, in addition to identifying conserved deletions and their likely origin. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>